Extremophilic Microbial Processing of Lignocellulosic Feedstocks to Biofuels, Value-Added Products, and Usable Power (Springer International Publishing, 2018)
This book presents a review and in-depth analyses of improved biotechnological processes emphasizing critical aspects and challenges of lignocellulosic biomass conversion into biofuels and value-added products especially using extremophiles and recombinant microorganisms. The book specifically comprises extremophilic production of liquid and gaseous biofuels (bioethanol, biobutanol, biodiesel, biohydrogen, and biogas) as well as value added products (e.g. single cell protein, hydrocarbons, lipids, exopolysaccharides, and polyhydroxyalkanoates). The book also provides the knowledge on how to develop safe, more efficient, sustainable, and economical integrated processes for enhanced conversion of lignocellulosic feedstocks to liquid and gaseous biofuels. Finally the book describes how to perform the techno-economical and life-cycle assessments of new integrated processes involving extremophiles. These modeling exercises are critical in addressing any deficiencies associated with the demonstration of an integrated biofuels and value-added products production process at pilot scale as well as demonstration on the commercialization scale. .